Formulation of Yellow Pumpkin Powder as an Instant Drink to Enhance Body Health - Surya, Sara; Rizal, Rosiana; Putri, Lusia Eka; Kamal, Sefrianita (Budapest International Research and Critics University, 2021)
The instant drink is processed products in powder form, easily soluble in water, practical in serving, and long shelf life due to their low water content and large surface area. In the current situation, a vitamin or drink that can improve the health of the body is needed. One of the compounds that can neutralize free radicals in the body as a trigger for a disease is β-carotene which has good antioxidant properties. One of the plants that contain high β-carotene is Yellow Pumpkin. It has a high nutritional content and fine fibre; thus, it is easy to digest. The method of making the instant drink is an oven drying method. This study aims to analyze β-carotene in yellow pumpkin, which is useful as an antioxidant using the UV-VIS spectrophotometry method. The absorbance of the β-carotene standard at a wavelength of 450 nm with distilled water as a blank. β-carotene standard is prepared by dissolving 0.2 g of potassium chromate in water to a volume of 100 ml.